Respiratory function in patients post-infection by COVID-19: a systematic review and meta-analysis - R. Torres-Castro (Pulmonology, 2021)
Background: Evidence suggests lungs as the organ most affected by coronavirus disease 2019 (COVID-19). The literature on previous coronavirus infections reports that patients may experience persistent impairment in respiratory function after being discharged. Our objective was to determine the prevalence of restrictive pattern, obstructive pattern and altered diffusion in patients post-COVID-19 infection and to describe the different evaluations of respiratory function used with these patients. Methods: A systematic review was conducted in five databases. Studies that used lung function testing to assess post-infection COVID-19 patients were included for review. Two independent reviewers analysed the studies, extracted the data and assessed the quality of evidence. Results: Of the 1973 reports returned by the initial search, seven articles reporting on 380 patients were included in the data synthesis. In the sensitivity analysis, we found a prevalence of 0.39 (CI 0.24–0.56, p < 0.01, I2 = 86%), 0.15 (CI 0.09–0.22, p = 0.03, I2 = 59%), and 0.07 (CI 0.04–0.11, p = 0.31, I2 = 16%) for altered diffusion capacity of the lungs for carbon monoxide (DLCO), restrictive pattern and obstructive pattern, respectively. Conclusion: Post-infection COVID-19 patients showed impaired lung function; the most important of the pulmonary function tests affected was the diffusion capacity.